FINANCIAL SECURITY OF THE TERRITORIES OF UKRAINE IN MODERN CONDITIONS: REGIONAL ASPECT - SAKHNO, Tetiana; SARANA, Lesya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the peculiarities of financing regions, cities, and united territorial communities in the conditions of martial law. Sources of funding of the territories are given, which are defined as: tax revenues, state subsidies, subventions, the State Fund for Regional Development, international loans, grants, participation in international projects, programs, sponsorship support. Their structure and changes caused by the war are analyzed. It was determined that the lion's share of local budgets, on average 70%, is made up of tax revenues. Another 25% are state transfers. The causes of significant economic disparities in the development of the country's territories have been determined. The impact of migration processes, business relocation on the development of regions as a whole and the filling of local budgets, in particular, is analyzed. Factors affecting the amount of funding for the functioning and development of regions, cities, and communities are given. In particular, the influence of preferential taxation on the filling of local budgets was considered. Changes in the principle of operation of the budget equalization system due to martial law are analyzed and presented. It was studied how the principles, sources and objects of funding of the regions changed during the martial law. The primary objects of financing were: the Armed Forces of Ukraine (assistance in material and technical support), territorial defence, internally displaced persons, citizen security (organization and arrangement of shelters), relocated business. It has been determined what advantages and opportunities have opened up for local self-government thanks to the Law of Ukraine No. 2390 "On Amendments to Chapter VI "Final and Transitional Provisions" of the Budget Code of Ukraine regarding strengthening the flexibility of local budgets and increasing the efficiency of decision-making." New rules for the distribution of funds from the state regional development fund were considered. It was determined that the population size and the GRP indicator used to be the indicators by which the norms for the distribution of finances were formed. In 2023, the distribution of funds from the fund is planned to be carried out according to the following principle: 50% of the funds of the fund will be distributed among all regions of Ukraine in equal parts, the other 50% will be distributed equally among the 11 regions of Ukraine that were most affected by military actions. The essence and prospects of financing the development of territories thanks to partner projects were studied.
Keywords: budgetary decentralization; financing of regions; tax revenues; state transfers; partnership projects